1997
DOI: 10.1038/sj.hdy.6881830
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of sexual proportion in experimental sex-ratio populations of Drosophila mediopunctata

Abstract: Sex-linked meiotic drive genes are expected to spread quickly in populations and may cause their extinction because of the lack of one sex. Theoretically, the most general evolutionary response to these genes is the spread of autosomal suppressors of meiotic drive because of Fisher's Principle, a mechanism of natural selection that would correct uneven sexual proportions. Such adaptive response depends on heritable autosomal variation for sexual proportion, which seems to be lacking in most species with chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Second, sex-ratio has a much greater effect on the rest of genome precisely because it affects the sex ratio, and thus, the transmission rates of different genomic compartments. In addition to favoring modifiers that reduce any fitness cost, sex-ratio favors modifiers that render the sex ratio more equal, as mandated by Fisher's principle [ 52 ]. The evolutionary cycle of distorter and suppressor could go on indefinitely as long as new sex-ratio mutations unaffected by existing suppressors can occur.…”
Section: Discussionmentioning
confidence: 99%
“…Second, sex-ratio has a much greater effect on the rest of genome precisely because it affects the sex ratio, and thus, the transmission rates of different genomic compartments. In addition to favoring modifiers that reduce any fitness cost, sex-ratio favors modifiers that render the sex ratio more equal, as mandated by Fisher's principle [ 52 ]. The evolutionary cycle of distorter and suppressor could go on indefinitely as long as new sex-ratio mutations unaffected by existing suppressors can occur.…”
Section: Discussionmentioning
confidence: 99%
“…The heritability of the primary sex ratio in most of these studies (all sex chromosome systems) was indistinguishable from zero (Falconer 1954;Edwards 1970;Bar-Anan and Robertson 1975;Foster and McSherry 1980;Toro and Charlesworth 1982;Hohenboken et al 1988). Heritabilities in the primary sex ratio have now been reported in a parasitic wasp (realized h 2 ϭ 0.15-0.17, Parker and Orzack 1985; parent-offspring h 2 ϭ 0.05-0.15, Orzack and Gladstone 1994) and in populations of Drosophila mediopunctata (parent-offspring h 2 ϭ 0.41, Varandas et al 1997; realized h 2 ϭ 0.20, Carvalho et al 1998) that have sex-linked segregation distortion.…”
Section: Heritability Of the Primary Sex Ratio Versus Heritability Ofmentioning
confidence: 98%
“…Finally, Varandas, Sampaio and Carvalho (1997) were able to estimate the heritability for the sexual proportion in the experimental populations. They showed that it was quite high (h 2 =41%) and due to autosomal variation, fulfilling a necessary condition for the evolution of the sexual proportion in response to natural selection.…”
Section: Sex-ratiomentioning
confidence: 99%